Arsenic removal from water through adsorption-A Review - Verma, Pankaj; Agarwal, Abhinay; Singh, V K (Recent Research in Science and Technology, 2014)
Arsenic is a commonly occurring toxic metal in natural systems. It is ahuman carcinogen in water over a wide range of pH values, having harmful effects on both human health andenvironment, even at low concentration. Because ofthis effect, the World Health Organization (WHO) and the US Environmental Protection Agency (USEPA) set the arsenic standard for drinking water at .010 ppm to protect consumers served by public water systems.Occurrence of arsenic contaminated water is reported in several countries like USA, China, Bangladesh, Mexico, Argentina, Poland, Canada, Hungary, Japan and India. The largest population at risk is in Bangladesh followed by India (West Bengal).There is no effective treatment for arsenic toxicity. Onlythe removal of arsenic from water can prevent the toxicity. A great deal of research over recent decades has been done to lower the concentration of arsenic in drinking water and still there is a need to develop low cost viable techniques. Existing major arsenic removal technologies include oxidation, adsorption, precipitation, coagulation andmembrane separation. This paper presents the review of current status of research in the area of arsenic removal from contaminated water and comparison of all technologies available with more emphasis on adsorption.